2016
DOI: 10.3390/ph9030057
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TRPM2 in ROS-Coupled Diseases

Abstract: Under pathological conditions such as inflammation and ischemia-reperfusion injury large amounts of reactive oxygen species (ROS) are generated which, in return, contribute to the development and exacerbation of disease. The second member of the transient receptor potential (TRP) melastatin subfamily, TRPM2, is a Ca2+-permeable non-selective cation channel, activated by ROS in an ADP-ribose mediated fashion. In other words, TRPM2 functions as a transducer that converts oxidative stress into Ca2+ signaling. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 115 publications
0
27
0
Order By: Relevance
“…It was shown that extracellular buildup of amyloid-β (Aβ) in Alzheimer's disease (AD) impairs endothelial structure and function through activation of the TRPM2, leading to intracellular Ca 2+ overload and vasomotor dysfunction [114]. TRPM2 is a transducer that converts oxidative stress into calcium signaling and plays an important role in ROS-coupled diseases [115]. On the other hand, exogenous H 2 O 2 increases [Ca 2+ ] i and decreases transmembrane electrical resistance in lung microvascular ECs via activation of TRPV4 through a mechanism that requires the Src kinase Fyn [116].…”
Section: Ros and Other Modulators Of The State Of Endotheliummentioning
confidence: 99%
“…It was shown that extracellular buildup of amyloid-β (Aβ) in Alzheimer's disease (AD) impairs endothelial structure and function through activation of the TRPM2, leading to intracellular Ca 2+ overload and vasomotor dysfunction [114]. TRPM2 is a transducer that converts oxidative stress into calcium signaling and plays an important role in ROS-coupled diseases [115]. On the other hand, exogenous H 2 O 2 increases [Ca 2+ ] i and decreases transmembrane electrical resistance in lung microvascular ECs via activation of TRPV4 through a mechanism that requires the Src kinase Fyn [116].…”
Section: Ros and Other Modulators Of The State Of Endotheliummentioning
confidence: 99%
“…TRPM2 detects warm temperatures and is implicated in thermal sensation and regulation [ 92 , 93 ]. Notably, TRPM2 is also activated by reactive oxygen species (ROS) and ADP-ribose (ADPR) produced during oxidative stress and ischemia, functioning as a sensor for oxidative stress [ 9 ]. Ca 2+ influx and Ca 2+ signaling triggered by TRPM2 activation during oxidative stress is critical to many pathological processes such as cytokine production, cell death and immune and inflammatory diseases [ 9 ].…”
Section: Trpm2mentioning
confidence: 99%
“…Of them, TRPV1–4 are mainly expressed in the sensory ganglia and skin responsible for thermo-sensation, pain and itch, whilst TRPV5 and TRPV6 are primarily expressed in the kidney and gastrointestinal tract and play a major role in Ca 2+ absorption and homeostasis [ 3 , 5 , 6 ]. The TRPM subfamily is the largest, consisting of eight members broadly expressed in a variety of cells and tissues, such as sensory ganglia, pancreatic beta cells, immune cells, the tongue, heart and kidney, and are critical for sensory physiology (e.g., heat (TRPM3), cold (TRPM8), taste (TRPM5) and light (TRPM1) sensing and detection) [ 5 ], insulin release (TRPM2, TRPM4 and TRPM5) [ 7 , 8 ], Mg 2+ homeostasis (TRPM6 and TRPM7), ischemic injury and inflammatory responses (TRPM2, TRPM4) [ 9 ]. TRPA1 is the sole member of the TRPA subfamily, implicated in pain, itch and inflammation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil granulocytes are among the few cells that are not equipped with poly(ADP-ribose)-Polymerases (PARPs; Sanghavi et al, 1998 ). Along with poly(ADP-ribose) glycohydrolases (PARGs), these are key enzymes involved in the formation of ADPR after oxidative damage to the DNA (e.g., reviewed by Yamamoto and Shimizu, 2016 ). Therefore, in many other cell types including neurons, ADPR-induced Ca 2+ influx through TRPM2 is a decisive element in the process that terminates in apoptosis after initiation by oxidative stress.…”
Section: Human Trpm2: History and Hallmarks Of An Exceptional Cation mentioning
confidence: 99%